2021
DOI: 10.12659/msm.930610
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Prolactin-Induced Protein Promotes Osteogenic Differentiation of Periodontal Ligament Stem Cells

Abstract: Background Periodontal ligament stem cells (PDLSCs) are promising seed cells for bone tissue engineering and periodontal regeneration applications. However, the mechanism underlying the osteogenic differentiation process remains largely unknown. Previous reports showed that prolactin-induced protein (PIP) was upregulated after PDLSCs osteogenic induction. However, few studies have reported on the function of PIP in osteogenic differentiation. The purpose of the present study was to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Though little is known about its exact physiological function, studies observed that prolactin-induced protein is able to bind to CD4 receptors of T lymphocytes or macrophages and the Fc fragment of immunoglobulin G, and therefore supposedly has immunomodulatory capabilities [ 51 , 52 ]. Its high expression on day 14 of osteogenic differentiation is in line with the findings of Li et al [ 53 ], where PIP upregulations were observed during the osteogenic induction of periodontal ligament stem cells (PDLSC). They concluded that the upregulation seems to be caused by dexamethasone, a glucocorticoid which is also part the StemPro ® Osteogenesis Differentiation Kit.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Though little is known about its exact physiological function, studies observed that prolactin-induced protein is able to bind to CD4 receptors of T lymphocytes or macrophages and the Fc fragment of immunoglobulin G, and therefore supposedly has immunomodulatory capabilities [ 51 , 52 ]. Its high expression on day 14 of osteogenic differentiation is in line with the findings of Li et al [ 53 ], where PIP upregulations were observed during the osteogenic induction of periodontal ligament stem cells (PDLSC). They concluded that the upregulation seems to be caused by dexamethasone, a glucocorticoid which is also part the StemPro ® Osteogenesis Differentiation Kit.…”
Section: Discussionsupporting
confidence: 89%
“…Dexamethasone supposedly stimulates PIP expression by a glucocorticoid receptor-dependent transcriptional activation. Moreover, they observed that a knockdown of PIP and its fibronectin-degrading properties even enhanced mineralization of PDLSC [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis induced by bacteria especially Gram-negative bacteria is the most prevalent chronic inflammatory disease worldwide [ 15 ]. Infections and the subsequent host immune responses have remodeled an aberrant microenvironment, which generally lead to the dysfunction of PDLSCs, which are the potential “seed cells” for periodontal regeneration applications and bone tissues engineering [ 16 , 17 ]. Interestingly, recent studies have reported that scathing PDLSCs may conduce to the perturbation of periodontal homeostasis [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIP is predominantly present within normal breast tissue, and its presence becomes lower to completely absent when the process of differentiation is lost due to the advancement of a tumor. The expression of PIP is closely connected with the differentiation of luminal epithelial cells in the mammary gland, a phenomenon that is induced by prolactin [ 22 , 23 , 24 ]. The existence of PIP under physiological and pathological conditions suggests that it is involved in many functional activities of cells.…”
Section: Pip: Structure Expression and Homeostatic Functionmentioning
confidence: 99%